Education outside the classroom as upstream school health promotion: 'adding-in' physical activity into children's everyday life and settings. Issue 3 (May 2022) - Bentsen, Peter; Mygind, Lærke; Elsborg, Peter; Nielsen, Glen; Mygind, Erik
Introduction: It is central for public health to answer questions related to how to change health and wellbeing in populations through interdisciplinarity and health in all policies and sectors. For a school physical activity promotion initiative to be acceptable and thus feasible, the buy-in of teachers is fundamental. Therefore, school physical activity promotion should be integrated into and support teaching activities. Aims: We discuss the use of education outside the classroom as a feasible pedagogical approach that integrates and promotes physical activity for school children. Methods: We present and discuss theoretical arguments and empirical evidence to argue and illustrate that education outside the classroom is a promising approach for promoting physical activity. Results: Education outside the classroom is characterised by regular curriculum-based experiential teaching activities outside the classroom with the inclusion of physical activity as a means to pedagogical ends. School subjects are taught outside the classroom drawing on problem-based learning and experiential education. Here, physical activity is integrated without compromising curriculum goals which increases teacher buy-in and thereby intervention acceptability and feasibility. Empirical evidence suggests that education outside the classroom increases boys' moderate to vigorous physical activity and girls' light intensity physical activity. We contend that the mechanisms are a mix of place, pedagogy and pupil motivations. Conclusions: Education outside the classroom is a feasible and acceptable approach to public health and physical activity promotion because it is integrated into children's everyday settings through curriculum time and applied broadly to child populations at a low cost. The practice of education outside the classroom is context-dependent and culturally bound, and practices therefore need to be adapted to the individual sociocultural context.